2007
DOI: 10.1088/0957-4484/19/03/035505
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial behaviour of single poly(N,N-dimethylacrylamide) chains as a function of pH

Abstract: We have studied the pH-dependent conformational behaviour of poly(N,N-dimethylacrylamide) (PDMAc) at silicon and gold surfaces using single-molecule force spectroscopy and a quartz crystal microbalance (QCM). Despite the pH dependence, nuclear magnetic resonance and titration experiments demonstrate that PDMAc is not a weak polybase. The interaction between single chains and a silicon surface (with native oxide layer intact) in aqueous solution was investigated using force spectroscopy. Single-molecule force m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Experiments were conducted in deionized water (15 MΩ resistivity, Elga PURELab option water purifier) at room temperature with a z-piezo velocity of 400 nm/s. Details of the MFP and the force-distance curve analysis can be found elsewhere [34,39]. The spring constant of each cantilever was characterized using the built-in thermal calibration method [40].…”
Section: Force Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments were conducted in deionized water (15 MΩ resistivity, Elga PURELab option water purifier) at room temperature with a z-piezo velocity of 400 nm/s. Details of the MFP and the force-distance curve analysis can be found elsewhere [34,39]. The spring constant of each cantilever was characterized using the built-in thermal calibration method [40].…”
Section: Force Spectroscopymentioning
confidence: 99%
“…For example, a single peak shows there is only one contact point between polymer and surface, indicating that the chain is mostly immersed in the solution, with only a small train of monomers on the surface, whereas a plateau suggests the chain takes a pancake conformation. More details can be found elsewhere [10,34,43].…”
Section: Force Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Greenfels and Wanger [29] built an analytical model to investigate the effect caused by the filler geometry (diameter and length) on the toughness, strength and stiffness of nanocomposites, and they found that theses material properties can be improved simultaneously by reducing the nanotube crosssectional aspect ratio (cross-sectional aspect ratio 5 diameter/length). Koratkar et al [30,31] reported that the addition of carbon nanotubes with an average length of 15 mm to an epoxy polymer matrix reduced the rate of crack growth when the nanocomposites were subjected to cyclic-fatigue loading. The increase in fatigue resistance was also demonstrated in a methylmethacrylate polymer modified with carbon nanotubes [32].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the addition of milled carbon fibers to a similar polymer gave no improvement in fatigue performance [33], indicating that the effect of using carbon nanotubes on the fatigue performance of polymer-based nanocomposites is substantially more efficient compared with the use of conventional carbon fibers. The main mechanism through which the addition of carbon nanotubes increases the observed toughness of polymer-based composites was identified in examinations on the fractography of nanocomposites [15,[28][29][30] as pullout of the nanotubes from the polymeric matrix when the crack faces open during crack propagation. The nanotube pullout mechanism involves interface debonding between nanotubes and the polymer matrix, followed by friction as the nanotubes are extracted from the matrix.…”
Section: Introductionmentioning
confidence: 99%